2017
DOI: 10.3390/molecules22050708
|View full text |Cite
|
Sign up to set email alerts
|

Selenium Speciation in the Fountain Creek Watershed (Colorado, USA) Correlates with Water Hardness, Ca and Mg Levels

Abstract: The environmental levels of selenium (Se) are regulated and strictly enforced by the Environmental Protection Agency (EPA) because of the toxicity that Se can exert at high levels. However, speciation plays an important role in the overall toxicity of Se, and only when speciation analysis has been conducted will a detailed understanding of the system be possible. In the following, we carried out the speciation analysis of the creek waters in three of the main tributaries—Upper Fountain Creek, Monument Creek an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…The interpretation of the 51 V NMR spectral data was supplemented by speciation calculations based on constants measured previously (Pettersson et al, 1983 ; Ehde et al, 1989 ; Selling et al, 1994 ). The species distribution diagrams were calculated by using HySS 2009 software (Alderighi et al, 1999 ; Carsella et al, 2017 ) and known speciation constants of the system at hand (Pettersson et al, 1983 ; Ehde et al, 1989 ; Selling et al, 1994 ). The citrate and the phosphate concentrations found in the Middlebrook 7H9 broth medium supplemented with 5% BSA, 2% dextrose, 5% catalase (ADC) enrichment, glycerol (0.2%, v/v), and Tween 80 (0.05%, v/v) were 0.48 and 24 mM, respectively ( Bbl tm , 2018 ).…”
Section: Methodsmentioning
confidence: 99%
“…The interpretation of the 51 V NMR spectral data was supplemented by speciation calculations based on constants measured previously (Pettersson et al, 1983 ; Ehde et al, 1989 ; Selling et al, 1994 ). The species distribution diagrams were calculated by using HySS 2009 software (Alderighi et al, 1999 ; Carsella et al, 2017 ) and known speciation constants of the system at hand (Pettersson et al, 1983 ; Ehde et al, 1989 ; Selling et al, 1994 ). The citrate and the phosphate concentrations found in the Middlebrook 7H9 broth medium supplemented with 5% BSA, 2% dextrose, 5% catalase (ADC) enrichment, glycerol (0.2%, v/v), and Tween 80 (0.05%, v/v) were 0.48 and 24 mM, respectively ( Bbl tm , 2018 ).…”
Section: Methodsmentioning
confidence: 99%
“…It is noted that almost all the concentrations of TSe-W in the wild areas were higher than those in the aquaculture areas, indicating that human activities have important effects on the concentration of selenium in fishpond environments. As limited by the sensitivity of HPLC-HG-AFS, no Se(IV) and Se(VI) were detectable in water, but numerous studies have revealed that Se(VI) is the main existing form in natural water (Carsella, Sanchez-Lombardo, Bonetti, & Crans, 2017;Serafimovska, Arpadjan, Stafilov, & Popov, 2011). Total mercury in water varied within 0.36 to 0.55 μg/L with an average value of 0.49 μg/L for the wild areas and 0.42 μg/L for the aquaculture areas.…”
Section: Species and Concentrations Of Selenium And Mercury In Watermentioning
confidence: 99%
“…The environmental levels of selenium (Se) are regulated and strictly controlled in the USA by the Environmental Protection Agency (EPA). The correlation between selenium and other elements is also important [ 19 ].…”
Section: Introductionmentioning
confidence: 99%